Efektifitas Pembelajaran Melalui Media Daring Ditinjau Dari Hasil Belajar Mahasiswa Pada Masa Pandemi Covid 19 - Ch. Dini Ika Handayani (HOME, 2020)
Coronavirus disease 2019 (Covid-19) outbreak that has hit 215 countries in the world, presents its own challenges for educational institutions, especially universities. To fight Covid-19, the government has banned universities from carrying out face-to-face (conventional) lectures and ordered to hold lectures or learning online. Whatsapp Group is one of the familiar and frequently used distance learning media. While Zoom Meeting application is a learning media using video so that it more resembles a face-to-face meeting. This study aims to see the effectiveness of Advanced Business Statistics learning by using Whatsapp Group media and Zoom Meeting application reviewed from student learning outcomes at STIE Bisnis Indonesia Solutions. This type of research is a quasi experiment using one group pretest-postest design. The sample of research is 4th semester students who took advanced business statistics courses as many as 100 people. Sample data is processed with descriptive analysis and average difference test using Wilcoxon Signed Rank Test and N-Gain Score. The results showed that Advanced Business Statistics Course Lecture at STIE Solusi Bisnis Indonesia using WhatsApp Group media and Zoom Meeting application is not effective when viewed from student learning results. This can be seen in the N-Gain value obtained a result of 0.16.